On internet, I was looking for the proof regarding the following relationship between $Y$ young's modulus,$\sigma$ poisson's ratio, and $B$ bulk modulus: $Y=3B(1-2\sigma)$, and I came across the following proof, which I have difficulty in understanding it.

Consider a cube subjected to three equal stresses S on the three faces The total strain in one direction or along one face due to the application of volumetric stress S is given as $$\text{linear Strain} = S/Y – \sigma S/Y –\sigma S/Y = S/Y( 1-2\sigma)$$ So $\text{linear Strain} =(S/E)( 1-2r)$. Now $\text{Volumetric Strain} = 3 \cdot \text{Linear Strain}$. So $\text{Volumetric Strain} = 3 (S/Y)( 1-2\sigma)$ Now by definition of bulk modulus of elasticity K. We have $K= \frac{\text{volumetric Stress}} {\text{volumetric Strain}}$. $K= \frac{S}{{(3(S/Y)( 1-2\sigma)}}$ , So $Y=3K(1-2\sigma)$

I am having main doubt regarding linear strain equation, especially why $–\sigma S/Y$ is being added two times. Rest of the proof is understandable to me. So please help me there. Moreover I want to ask is there, any simpler proof for this equation? Also, while finding/researching, I can't come up with proof for another similar equation: $Y=2\eta(1+\sigma)$, where $\eta$ is shear modulus. So I want help here too.


1 Answer 1


Hre is a general set of relations:

Start from the isotropic stress-strain relation $$ \sigma_{ij} = \lambda \delta_{ij} e_{kk} + 2\mu e_{ij} $$ in terms of the Lame constants $\lambda$, $\mu$. By considering particular deformations, we can express the more directly measurable bulk modulus, shear modulus, Young's modulus and Poisson's ratio in terms of $\lambda$ and $\mu$.

The bulk modulus bulk modulus $\kappa$ is defined by $$ dP =-\kappa \frac {dV}{V}, $$ where an infinitesimal isotropic external pressure $dP$ causes a change $V\to V+dV$ in the volume of the material. This applied pressure corresponds to a surface stress of
$\sigma_{ij}=-\delta_{ij}\,dP$. An isotropic expansion away from the origin displaces points $x_i\to x_i+\eta_i$ in the material so that $$ \eta_i =\frac 13 \frac {dV}{V}x_i. $$ The strains $$ e_{ij}= \frac 12 (\partial_i\eta_j+\partial_j \eta_i) $$ are therefore given by $$ e_{ij} = \frac 13 \delta_{ij} \frac {dV}{V}. $$ Inserting this strain into the stress-strain relation gives $$ \sigma_{ij}= \delta_{ij}(\lambda +\frac 23 \mu)\frac {dV}{V}= - \delta_{ij} dP. $$ Thus $$ \kappa= \lambda+\frac 23 \mu. $$

To define the shear modulus, we assume a deformation $\eta_1 = \theta x_2$, so $e_{12}=e_{21}=\theta/2$, with all other $e_{ij}$ vanishing.

The applied shear stress is $\sigma_{12}=\sigma_{21}$. The shear modulus, is defined to be $\sigma_{12}/\theta$. Inserting the strain components into the stress-strain relation gives $$ \sigma_{12} =\mu\theta, $$ and so the shear modulus is equal to the Lame constant $\mu$. We can therefore write the generalized Hooke's law as $$ \sigma_{ij} = 2\mu(e_{ij} -{\textstyle{\frac 13}} \delta_{ij} e_{kk}) +\kappa e_{kk} \delta_{ij}, $$ which reveals that the shear modulus is associated with the traceless part of the strain tensor, and the bulk modulus with the trace.

Young's modulus $Y$ is measured by stretching a wire of initial length $L$ and square cross section of side $W$ under a tension $T=\sigma_{33}W^2$.

We define $Y$ so that
$$ \sigma_{33} = Y\frac {dL}{L}. $$ At the same time as the wire stretches, its width changes $W\to W+dW$. Poisson's ratio $\sigma$ is defined by $$ \frac{dW}{W}=-\sigma \frac{dL}{L}, $$ so that $\sigma$ is positive if the wire gets thinner as it gets longer. The displacements are $$ \eta_3 = z \left(\frac {dL}{L}\right),\nonumber\\ \eta_{1}=x \left(\frac{dW}{W}\right) = - \sigma x \left(\frac{dL}{L}\right),\nonumber\\ \eta_{2} = y \left(\frac{dW}{W}\right)= - \sigma y \left(\frac{dL}{L}\right), $$ so the strain components are $$ e_{33} = \frac {dL}{L},\quad e_{11}=e_{22} = \frac{dW}{W}=-\sigma e_{33}. $$ We therefore have $$ \sigma_{33} = (\lambda(1-2\sigma) +2\mu)\left(\frac {dL}{L}\right), $$ leading to $$ Y= \lambda(1-2\sigma)+2\mu. $$ Now, the side of the wire is a free surface with no forces acting on it, so $$ 0=\sigma_{22}=\sigma_{11} = (\lambda(1-2\sigma) -2\sigma \mu)\left(\frac {dL}{L}\right). $$ This tells us that $$ \sigma =\frac 12 \frac{\lambda}{\lambda+\mu}, $$ and $$ Y= \mu\left(\frac{3\lambda+2\mu}{\lambda+\mu}\right). $$ The desiired relations $$ Y= 3\kappa(1-2\sigma),\nonumber\\ = 2\mu(1+\sigma), $$ now follow by simple algebra from those above.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.